QUIZIZZ PAPER MODE IS NEW : STUDENTS’ PERCEPTION OF USING E-TOOL OF LANGUAGE ASSESSMENT IN EFL CLASS - Lisa’adah Al Husnah; Dwi Fita Heriyawati; Sonny Elfiyanto (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2023)
In recent years, educational technology has played a substantial part in revolutionizing teaching and learning practices. Quizizz has gained prominence for interactive features. Quizizz launched Quizizz Paper Mode as a new featur. This study focused on students’ perception of using Quizizz Paper Mode as a tool of language assessment in EFL Class. This study aimed to unveil the unique insights and experiences of students regarding Quizizz Paper Mode as a tool for language assessment. This study employed a qualitative approach through descriptive analysis. The data collected by semi structured interview given to gather data from a diverse group of students. A varied group of students set out to gather a wide variety of data samples. The study's scope was enhanced by their diverse activeness and motivation during learning English. From the data caught that the students perceive Quizizz Paper Mode as a interesting tool of language assessment, encourage their confidence, increasing their motivation and enhancing reading ability. In conclusion, this article shed light on the potential of Quizizz Paper Mode as a tool for engaging language assessment in EFL Class. The findings offered valuable insights for educators seeking innovative approaches to language assessment in the digital era.